1972
DOI: 10.2134/jeq1972.00472425000100010014x
|View full text |Cite
|
Sign up to set email alerts
|

Edaphic Aspects of the Disposal of Unused Pesticides, Pesticide Wastes, and Pesticide Containers

Abstract: With a view toward the disposal of large quantities of pesticides in the soil, the biodegradation and the effects on the soil microflora of 20 single analytical grade and formulated pesticides and 7 mixtures of formulations were investigated in a calcareous West Point loam. The soil was amended with 11,227 kg/ha (5 tons/acre) of the respective active ingredient(s) and subsequently incubated for 56 days. The extent of biodegradation was estimated from the CO2 evolved during the incubation and the effects on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Niclofen and carbofuran containers had the highest residues, 2.2% and 2.7%, respectively, of the original contents; these values agree well with those obtained in the Cooper study (2.2-2.8%) reported by Stojanovic et^ al_. 1 . These amounts of material are considerable and for efficiency should have been rinsed into the spray tank by the operators.…”
Section: Please Scroll Down For Articlesupporting
confidence: 91%
“…Niclofen and carbofuran containers had the highest residues, 2.2% and 2.7%, respectively, of the original contents; these values agree well with those obtained in the Cooper study (2.2-2.8%) reported by Stojanovic et^ al_. 1 . These amounts of material are considerable and for efficiency should have been rinsed into the spray tank by the operators.…”
Section: Please Scroll Down For Articlesupporting
confidence: 91%
“…Twenty-four organisms required 10,000 ppm 2,4,5-T for growth restriction to occur. In the study by Stojanovic, Kennedy, and Shuman (1972), 5,000 ppm of an equal mixture 2,4-D and 2,4,5-T inhibited growth of bacteria and actinomycetes but the total number of fungi increased during the 56-day incubation period. Kearney, Woolson, and Ellington (1972) in the laboratory studied the persistence of TCDD in two soils, Lakeland sand and Hagerstown silty clay loam, at three rates of application(l, 10, and 100 ppm) for 360 days.…”
Section: Description Of Action a Generalmentioning
confidence: 92%
“…Colmer (1953) found that 5,000 ppm 2,4-0 were at first inhibitory to a bacterium, but after subculturing three times the organisms grew rapidly in the 5,000 ppm concentration. Stojanovic, Kennedy, and Shuman (1972) added a mixture of 2;4-D and 2,4,5-T (similar to the formulation of herbicide Orange) to soil at a concentration of 5 tons/acre (5,000 ppm in top 6 inches of soil). Seventy-eight percent of the herbicide carbon was given off as carbon dioxide in 56 days.…”
Section: Description Of Action a Generalmentioning
confidence: 99%
“…Twenty-six species were not inhibited by 10,000 ppm 2,4-D. Twenty-four organisms required 10,000 ppm 2,4,5-T for growth restriction to occur. In the study by Stojanovic, Kennedy, and Shuman (1972), 5,000 ppm of an equal mixture 2,4-D and 2,4,5-T inhibited growth of bacteria and actinomycetes but the total number of fungi increased during the 56-day incubation period. Kearney, Woolson, and Ellington (1972) in the laboratory studied the persistence of TCDD in two soils, Lakeland sand and Hagerstown silty clay loam, at three rates of application l, lO, and 100 ppm) for 360 days.…”
mentioning
confidence: 92%
“…Colmer (1953) found that 5,000 ppm 2,4-D were at first inhibitory to a bacterium, but after subculturing three times the organisms grew rapidly in the 5,000 ppm concentration. Stojanovic, Kennedy, and Shuman (1972) added a mixture of 2,4-D and 2,4,5-T (similar to the formulation of herbicide Orange) to soil at a concentration of 5 tons/acre (5,000 ppm in top 6 inches of soil). Seventy-eight percent of the herbicide carbon was given off as carbon dioxide in 56 days.…”
mentioning
confidence: 99%